2017
DOI: 10.5194/bg-14-241-2017
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of microbial activity and ash deposition to post-fire nitrogen availability in a pine savanna

Abstract: Abstract. Many ecosystems experience drastic changes to soil nutrient availability associated with fire, but the magnitude and duration of these changes are highly variable among vegetation and fire types. In pyrogenic pine savannas across the southeastern United States, pulses of soil inorganic nitrogen (N) occur in tandem with ecosystem-scale nutrient losses from prescribed burns. Despite the importance of this management tool for restoring and maintaining fire-dependent plant communities, the contributions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 54 publications
(83 reference statements)
1
22
0
Order By: Relevance
“…Because we did not analyze the community composition of decomposing microbes [43], we cannot exclude the possibility that differences in decomposer abundance and/or composition between destination fire regimes influenced decomposition. We also cannot discount the possibility that differences in microbial activity influenced decomposition, although previous work has found that net mineralization and net nitrification rates were not influenced by time since fire [27]. While we observed fast decomposition of understory species in triennially burned destination environments, and fast decomposition of triennial understory litter, we did not detect significant interactions between litter source and destination environment showing enhanced decomposition of triennial litter decomposing in triennially burned sites, or “home” litter [4446].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Because we did not analyze the community composition of decomposing microbes [43], we cannot exclude the possibility that differences in decomposer abundance and/or composition between destination fire regimes influenced decomposition. We also cannot discount the possibility that differences in microbial activity influenced decomposition, although previous work has found that net mineralization and net nitrification rates were not influenced by time since fire [27]. While we observed fast decomposition of understory species in triennially burned destination environments, and fast decomposition of triennial understory litter, we did not detect significant interactions between litter source and destination environment showing enhanced decomposition of triennial litter decomposing in triennially burned sites, or “home” litter [4446].…”
Section: Discussionmentioning
confidence: 91%
“…Fire can also impact litter decomposition if decomposer microbe populations shift [25] or if the local microbial community is best-adapted to decomposing local litter [26]. Finally, post-fire changes to nutrient availability in mineral soil [19, 27] may alleviate nutrient-limitation and increase activity of decomposing microbes. Fires that incompletely burn woody biomass may produce black carbon or biochar [28], which may increase soil microbial biomass and alter microbial and invertebrate composition by influencing soil pH and improving localized soil fertility [2931].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we expect individuals that escape the fire trap by growing quickly to be widely distributed across the landscape. If local resource availability is responsible for the variability in the growth rate of resprouts, as has been suggested (Grady andHoffmann 2012, Freeman et al 2017), it must be acting primarily at spatial scales smaller than the 50-m transects sampled here, or at temporal scales finer than the fire return interval (e.g., Wilson et al 2002, Schafer and Mack 2010, Ficken and Wright 2017. This pattern in growth rates may reduce spatial aggregation of mature stems somewhat, but the effect is likely small owing to the relatively small influence that variability in growth rate has on escape success.…”
Section: Implications For Savanna Spatial Structurementioning
confidence: 71%
“…The pulse of rain could have affected to movement of nutrients beyond the depths studied, the degree to which this affected the results is not known. A more radical hypothesis that fires temporarily depress plant uptake of N for and thereby enhance soil nutrient pools from reduced demand was proposed by Ficken and Wright [29], in their study of N mineralization rates in longleaf pine stands in eastern North Carolina. A period of depressed plant demand followed by a resumption or accelerated demand could help explain our intra-annual observation of peak nutrient pools after burning followed by depression below pre-burn conditions.…”
Section: Discussionmentioning
confidence: 99%